A Dynamic Non-interference Trust Chain Model Based on Security Process Algebra - Xiaoxing Wang; Xiangying Kong; Xuebing Chen (Institute of Advanced Engineering and Science, 2014)
Trust Chain is the key technology of Trusted Computing. For lack of comprehensive theoretical model of Trust Chain, A dynamic Trust Chain Model is proposed based on Security Process Algebra and Non-interference. Then, give the formal description and proof of the model. Finally, Modeling Intel TXT according to the new model semantics and verify the security attributes of the model by automated verification tool.DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3206